Insights on the inhibition properties of Jatromollistatin (a cyclic heptapeptide) against Crotalus adamanteus metalloendopeptidase using molecular docking analysis - Jucá, Thiago Lustosa; Ramos, Márcio Viana; Cilli, Eduardo Maffud [UNESP]; Neto, Antônio Eufrásio Vieira; Mackessy, Stephen P.; Monteiro-Moreira, Ana Cristina Oliveira (My University, 2022)
Jatropha mollissima is endemic to Brazil and is used for traditional medicinal purposes, including the treatment of snakebite. In this study, latex obtained from this plant was fractioned using reversed-phase chromatography, and the fractions were then screened for peptides. A 755 g/mol peptide was obtained, and MS/MS analyses indicated it had a cyclic sequence (Pro-Leu-Gly-Val-Leu-Leu-Tyr). This peptide sequence was present in the Jatropha genome database, and an identity value of 90.71%, an E-value of 0.0, and a score of 883 with NO-associated protein 1/chloroplastic/mitochondria of Jatropha curcas were obtained from the NCBI nonredundant protein sequence (nr) database. Molecular docking analyses performed with the peptide against a metalloendopeptidase belonging to Crotalus adamanteus snake venom suggested the cyclic peptide establishes favorable interactions with the catalytic site of the enzyme. Therefore, it could inhibit enzyme catalysis. This belief was corroborated by the formation of 6 hydrogen bonds with the linear form of the peptide. Tighter complexation of the cyclic form (41 kcal/mol more energetic) revealed better spatial blocking. The linear form outperformed the cyclic form in complexing the required energy, recruiting more catalytic residues (6/2), and in establishing more hydrogen bonds (6/3). However, cyclic folding provided a more significant spatial block within the catalytic site. The set of results suggests that the cycle peptide, here called Jatromollistatin, which was previously described as jatrophidin and pohlianin A in two other species of Jatropha, is a promising candidate to inhibit venom proteases. This belief is corroborated by the topical use of the latex for initial treatment of snakebites.
Keywords: latex; laticifers; orbitides; snake venom; solid phase extraction